The concept of the elect nation in Byzantium - Eshel, Shay (Medieval Mediterranean Ser., 2018)
"In The Concept of the Elect Nation in Byzantium, Shay Eshel shows how the Old Testament model of the ancient Israelites was a prominent factor in the evolution of Roman-Byzantine national awareness between the 7th and 13th centuries. The Byzantines' interpretation of the 7th century epic events as manifestations of God's wrath enabled them to incorporate the events into a paradigm which they now embraced: the Old Testament paradigm of the Israelite Elect Nation's complex relationship with God, a cyclic relation of sin, wrath, punishment, repentance and salvation. The Elect Nation concept enabled the Byzantines to express the shift in their collective identity toward a shrunken, yet more clearly defined, national awareness"--